KONSTRUKSI MEDIA - Ponco Anggoro, Albertus Rusputranto (Institut Seni Indoensia Surakarta, 2015)
Media institutions were never really neutral. They keep partisanship and ideology stand on each. Media also never really according to the broadcast media producers. Media has the power to menyempal and interpreted differently by the audience. Even so media or media agency always tries to frame (framing) of their products, constructing reality. The media, especially news, are often regarded as a representation of reality. By using the framing analysis terkuaklah construction of reality that media have tried to build on the audience and the resistance, such as what might be done spectators.Keywords: media, construction, framing analysis, reality.